2018
DOI: 10.1007/s00441-018-2835-9
|View full text |Cite
|
Sign up to set email alerts
|

Prosaposin and its receptors are differentially expressed in the salivary glands of male and female rats

Abstract: Salivary glands produce various neurotrophins that are thought to regulate salivary function during normal and pathological conditions. Prosaposin (PSAP) is a potent neurotrophin found in several tissues and various biological fluids and may play roles in the regulation of salivary function. However, little is known about PSAP in salivary glands. As the functions of salivary glands are diverse based on age and sex, this study examines whether PSAP and its receptors, G protein-coupled receptor 37 (GPR37) and GP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Although Psap is mainly localized in lysosomes, it can also be secreted, and it has been found in several fluids including serum ( Hineno et al, 1991 ). Psap is expressed in salivary glands and its levels differ based on the type of gland, acinar cells, age, and sex ( Islam et al, 2018 ). It has been demonstrated that Psap −/− mice develop inflammation, plaque formation and show a reduction of oxidative phosphorylation thus pointing out Psap as a potential therapeutic target for atherosclerosis ( van Leent et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although Psap is mainly localized in lysosomes, it can also be secreted, and it has been found in several fluids including serum ( Hineno et al, 1991 ). Psap is expressed in salivary glands and its levels differ based on the type of gland, acinar cells, age, and sex ( Islam et al, 2018 ). It has been demonstrated that Psap −/− mice develop inflammation, plaque formation and show a reduction of oxidative phosphorylation thus pointing out Psap as a potential therapeutic target for atherosclerosis ( van Leent et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another suspected peptide ligand with an EC 50 of 7.0 nM for GPR37 is prosaposin (PSAP), a multifunctional protein precursor to saposin A–D, that internally regulates lysosomal enzyme function and externally acts as a neuroprotective and glio-protective secretory factor. ,, It has been found that extracellular PSAP is necessary for the partitioning of GM1 ganglioside-containing lipid rafts in the plasma membrane of live cells expressing turbo green fluorescent protein-tagged (tGFP) GPR37 . Lipid rafts are specialized structures on the plasma membrane enriched in cholesterol, certain gangliosides, and lipids, and these membrane domains can coordinate the signaling of membrane receptors, including GPCRs .…”
Section: Gpr37 Pharmacology and Potential Ligandsmentioning
confidence: 99%